Pengaruh Kualitas Makanan, Suasana dan Kewajaran Harga Terhadap Kepuasan Pelanggan Pada Cafe Coklat Klasik Joyogrand Malang (Studi pada Mahasiswa Universitas Islam Malang) - Widyan Violita; Rois Arifin; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe development of retail business in Indonesia which is rapidly developing makes competition increasing, every business person will compete to make his product a product that is in great demand by consumers. The rise of culinary business and the mushrooming of cafes in Malang and the huge potential that exists has made businesses create creativity to make their businesses appear different in terms of the quality of the food provided, the atmosphere of the cafe served and the reasonableness of the prices offered. This study aims to determine the effect of food quality, atmosphere and fairness of prices on customer satisfaction at Joyogrand Coklat Klasik Cafe Malang. The population in this study were Malang Islamic University Students who had visited the Coklat Klasik Cafe Joyogrand Malang with a total sample of 85 respondents. Testing the hypothesis in this study using multiple linear regression analysis. The results showed that the variables of food quality, atmosphere and fairness of prices simultaneously affected customer satisfaction. food quality and price reasonableness variables have a positive and significant effect on customer satisfaction, while price reasonableness variables have no positive and significant effect on customer satisfaction. Keywords: Food Quality, Atmosphere, Price Fairness, Customer Satisfaction.